2018
DOI: 10.1111/his.13710
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of PD‐L1 expression in matched urothelial bladder cancer specimens

Abstract: Urothelial bladder cancer patients showed fair agreement of PD-L1 assay outcome in cystectomies and matched TURB or lymph node specimens. PD-L1 expression was discordant more often after neoadjuvant therapy. Therefore, immune-checkpoint inhibitor studies should take into account specimen type and neoadjuvant therapy in assessing the predictive value of PD-L1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 13 publications
3
16
0
1
Order By: Relevance
“…Numerous studies confirm the efficacy of inhibitors of control points in cancer immunotherapy [20][21][22][23][24][25][26]. However, not all patients respond to anti-PD-L1 therapy to the same extent which highlights the need to search for novel biomarkers to further stratify the treatment groups [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies confirm the efficacy of inhibitors of control points in cancer immunotherapy [20][21][22][23][24][25][26]. However, not all patients respond to anti-PD-L1 therapy to the same extent which highlights the need to search for novel biomarkers to further stratify the treatment groups [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The use of patient material for scientific purposes was approved by the local Medical Research Ethics Committee (Rotterdam, Netherlands, MEC-2014-553). All haematoxylin and eosin (HE) slides were reviewed by a genitourinary pathologist (GvL), who monitored the following: grade (WHO1973 and 2016), pT stage (TNM 8th edition), surgical margin status, presence of carcinoma in situ (CIS), vascular invasion (VI), and presence of variant histology (squamous, glandular, neuroendocrine, sarcomatoid) [12]. In the present study, whole tissue slides were newly stained with the PD-L1 SP263 assay and compared to PD-L1 SP142 stainings, which had been performed on the same slides and published previously [12].…”
Section: Patient Selection and Pathological Reviewmentioning
confidence: 99%
“…However, little is known about the variability of PD-L1 expression among different tumour tissues from individual patients [10,11]. Previously, we found poor concordance of PD-L1 expression in urothelial cancer as determined in matched transurethral resection of the bladder tumour (TURBT), RC, and lymph node metastasis (LN) using the VENTANA PD-L1 (SP142) assay [12]. The PD-L1 (SP142) assay has been used as companion diagnostic for atezolizumab and is based on PD-L1 expression on tumour-associated immune cells (IC) only.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of clinical trials have demonstrated a significant correlation between PD-L1 expression in some tumors and the effectiveness of treatment using immune checkpoint inhibitors (ICI) [14][15][16][17][18][19], especially in early stages of the disease [20], and in combination therapies [21]. However, some patients who meet the criteria for therapy do not respond well to anti-PD-L1 treatment [22,23]. Thus, finding new eligibility criteria for immunotherapy to increase its efficacy and safety is paramount.…”
Section: Introductionmentioning
confidence: 99%